Positive evolution in economic forecasting. Case study: the evolution of a company’s capital - POPESCU, Ion; UNGUREANU, Laura; MATEI, Viorel; VELTER, Victor (Annals of Spiru Haret University. Economic Series, 2010)
For the economic sciences, mainly for the planning and organization disciplines, the models display a range of varieties. For the last decades, though, the mathematics-based models seem to be the trend, partly because of their ability to rigorously concentrate the essentials and also to be programmed via the computer-based techniques, thus creating together an unheard of instrument of scientific investigation, a resourceful ‚extension’ of human intelligence. The article herein presents certain medium-term prognosis, via the dynamic modelling, elements of bifurcation theory and the Xpp software. The case study has been the object of a research contract with the business environment.